Tourism and Hospitality: Academia and Industry Interface - Kunwar, Ramesh Raj; Ulak, Nimesh (Journal of Tourism & Adventure, 2023)
The purpose of this study is to elaborate on the relationship between academia and industry. There is found a reciprocal relationship between academia and industry. Most of the studies have focused on the industry academia linkages from experiences of developed countries and those studies are not related to academia and tourism and hospitality relationships which are published in policy research. This study is based on exploratory research. Desktop research is carried out to collect secondary data to understand the collaboration and gap between academia and industry as there are many hidden problems in the process of producing the suitable manpower for the industry by academia and industry’s expectation from academia. Almost, the published literature is used in this research. This study is the outcome based on finding solutions to these research questions: how academia and industry collaboration in tourism and hospitality sectors is trending in the world? And what is the gap between these two arenas? This study aims to explore the interface between academia and industry (university and tourism and hospitality industry) which is very useful for providing knowledge, employment, and nation’s development. This study includes introduction, university and industry interface, tourism academia and industry interface, literature review, personology and professionalism, career commitment, collaboration and bridging gap, methodology, discussions, conclusion, and recommendations.